RECONSTRUCTION OF CONSUMER PROTECTION LAW IN MAKING THE BALANCE BUSINESS BASED BUSINESS AND CONSUMER VALUE OF JUSTICE - Ramon Nofrial; Darwinsyah Minin (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
The existence of Law No. 8 of 1999 on Consumer Protection guarantee the fulfillment of the rights of consumers to consume goods and services produced by businesses, as well as achieving a balance between consumer and business. Specifications are preskriftif analytical research. This study is a prescriptive offered the concept to solve a problem, highlight something (object) aspired or should be. Is a descriptive analysis, which is to describe all the symptoms and the facts and analyzing the problems that exist in the present. In respect of consumer protection in realizing the balance of businesses and consumers based on values of justice as an effort towards a welfare state based on Pancasila and the Constitution NRI Year 1945 made to the monitoring of the use clause like to give certain restrictions that do not diminish the rights of consumers, the application of strict liability businesses ( strict liability), consumer dispute resolution pursuant to Act No. 8 of 1999, not tort (KUHPdt), and the addition of Article 45 in paragraph (2) which states: in the consumer dispute resolution in civil and criminal can not be charged back, before businesses found not guilty, and Article 63 paragraph (1) reconstructed into: criminal sanctions as referred to in Article 62, can be imposed additional penalties, such as: Deprivation of certain goods; Verdict; Payment of compensation; and the obligation of withdrawal of goods from circulation. Keyword: Consumer Protection, Balance, Businessmen, Consumer, The Value Of  Justice